Critical Perspectives in English Language Teaching, What is Coming? - Angela Patricia Velásquez Hoyos; Luis Herney Villegas López (Asociación Colombiana de Profesores de Ingles, 2024)
This reflective article examines the emerging tendencies in critical perspectives within English Language Teaching (ELT). The article begins by providing a brief historical overview of ELT's critical pedagogies and discussing its perspectives in the post-pandemic era. It highlights the need for critical approaches that address power dynamics, social inequalities, and ideological influences. In addition, new trends imply integrating cultural aspects that favor students' identity and culture, and more dynamic bilingual practices to promote inclusive, socially just, multilingual, and transformative language learning environments. The article concludes by emphasizing the importance of ongoing reflection, professional development, and collaboration among ELT practitioners to incorporate critical perspectives effectively in the classroom.